Health Screening and Education for Non-Communicable Disease (NCD) Prevention and Early Detection of Cognitive Impairment among Elderly in Urban Communities - Azhari Umar Siregar; Sri Raudoh Rezki MR; Desi Meliana Gultom; Feggy Yustika Sitinjak; Rahmat Rizki Siregar; Seri Astuti Hasibuan (PT Inovasi Pratama Internasional, 2026)
This community service program aimed to conduct health screenings and provide educational interventions for non-communicable disease (NCD) prevention and early detection of cognitive impairment among elderly populations in Tapanuli Selatan Regency. The program involved 60 elderly participants (mean age 68.4 ± 6.2 years) from several villages within the working area of Puskesmas Pintu Padang. Screening methods included physical and biochemical examinations (blood pressure, random blood glucose, total cholesterol, and uric acid levels) as well as cognitive function assessments using the Mini-Mental State Examination (MMSE) and Clock Drawing Test (CDT). Results revealed that hypertension (65.0%), hyperglycemia (43.3%), and hypercholesterolemia (35.0%) were the most prevalent NCD risk factors, with 73.3% of participants having at least two risk factors. Cognitive impairment was identified in 25.0% of participants (16.7% mild, 8.3% moderate). Educational sessions successfully improved participants' knowledge regarding NCD prevention and cognitive health maintenance. The integrated screening and educational approach proved effective for early detection and health promotion in rural communities. Regular implementation of such programs, strengthened referral pathways to primary health centers, and continuous health education are essential strategies for improving elderly health outcomes in Tapanuli Selatan.